Strategic trade and industrial policy towards dynamic oligopolies - Neary, J; Leahy, D (Blackwell Publishing, 2000)
We characterise optimal trade and industrial policy in dynamic oligopolistic markets. If governments can commit to future policies, optimal first-period intervention should diverge from the profit-shifting benchmark to an extent which exactly offsets the strategic behaviour implied by Fudenberg and Tirole's ‘animal spirits’ taxonomy of business strategies. Without government commitment, there is an additional basis for intervention, whose sign depends on the strategic substitutability between future policy and current actions. We consider a variety of applications (to R&D; spillovers, consumer switching costs, etc.) and also extensions to constrained second-best policies.